A large marine Caribbean mushroom field: description of Eudistoma amanitum sp. nov. (Ascidiacea: Polycitoridae) - Paiva, Sandra Vieira; Da Rocha, Rosana Moreira (Zootaxa, 2018)
Numerous colonies of Eudistoma amanitum sp. nov. have been collected in Caribbean waters. The colonies resemble the groups of mushrooms from the Amanita genus and there are different color morphs. The discussion includes comparison with other species with similar shape.